The Westminster dictionary of theological terms - McKim, Donald K. (Louisville, Kentucky : Westminster John Knox Press, 2014)
"This second edition of the Westminster Dictionary of Theological Terms provides a comprehensive guide to nearly 7,000 theological terms, 1,000 more terms than the first edition. McKim's succinct definitions cover a broad range of theological studies and related disciplines: contemporary theologies, biblical studies, church history, ethics, feminist theology, global theologies, hermeneutics, liberation theology, liturgy, ministry, philosophy, philosophy of religion, postcolonial theology, social sciences, spiritually, worship, and Protestant, Reformed, and Roman Catholic theologies. This new edition also includes cross-references that link readers to other related terms, commonly used scholarly abbreviations and abbreviations for canonical and deuterocanonical texts, an annotated bibliography, and a new introductory section that groups together terms and concepts, showing where they fit within particular theological categories. No other single volume provides the busy student, and the theologically experienced reader, with such easy access to so many theological definitions. "--
Includes bibliographical references.
Keywords: Theology -- Dictionaries